STANDARDIZATION OF SEED BASED GENOTYPING SYSTEM FOR GENETIC PURITY TESTING IN MAIZE - P. SUJATHA and D. BHADRU, M. NEELOTHPALA, K. JHANSI RANI, S. VANISRI (The Journal of Research, PJTSAU, 2023)
DNA based characterization of maize genotypes has become the easiest and fastest approach to identify genetic purity as compared to phenotyping. High-quality DNA is a prerequisite for molecular biology experiments and thus DNA extraction is oneof the most important steps for several experiments. The conventional DNA source for genotyping is the leaf which requires atleast 2 weeks waiting period from seed planting to leaves sampling. Collection of leaves from the field and labeling are the steps which require time in leaf DNA-based genotyping. The objective of this study is to describe a DNA extraction protocol from seed ofhybrids and inbred lines of maize and to determine the suitability of extracted DNA for Polymerase Chain Reaction (PCR). In thepresent study, the protocol was developed for extracting high quality genomic DNA from seeds with minor modifications without the usage of liquid nitrogen. The concentration of DNA extracted from seeds ranged from 400 ng/μl to 800ng/μl. The results revealed that DNA extracted from seeds was suitable for SSR-PCR analysis. This seed-based method of genomic DNA extraction takes less than 24 hours from sampling to quantification and genotyping. It also avoids germination and waiting for leaf sampling and saves field space.